PERSEBARAN PRONOMINA PENUNJUK DALAM BAHASA MELAYU DI KALIMANTAN BARAT: KAJIAN GEOLINGUISTIK - Wiyanda, Syarifah Shafara; Asfar, Dedy Ary; Syahrani, Agus (Jurnal Pendidikan dan Pembelajaran Khatulistiwa (JPPK), 2024)
The research objectives is to describe the distribution of, pointer pronomina in Malay languages in West Kalimantan based on GIS. This research uses qualitative descriptive method. Criteria for selecting informants: aged 20"”40 years, active speakers of the Malay language of the region under study, physically mentally healthy, do not have defects in speech organs hearing organs, and have good internet access. Informant selection technique: snowball sampling technique through social media. The method used: conversational method with basic techniques of interview techniques and advanced techniques of open chats, note-taking techniques and recording techniques. Two data validity checking techniques: observation persistence and referential adequacy. The results found:The lexicon "ini" has 3 variations. The lexicon "itu" has 3 variations. The lexicon "di sini" has 2 variations. The lexicon "kesini" has 1 variation. The lexicon "ke situ" has 1 variation. The lexicon "di sana" has 3 variations. The lexicon "begini" has 3 variations. The lexicon "begitu" has 3 variations.